A Review of Severe Acute Respiratory Syndrome Coronavirus 2 and Pathological Disorders in Patients - Ghorbat Saleh Ali; Betul Ozdemir; Zeliha Selamoglu (Research Center for Rational Use of Drugs (RCRUD), 2021)
Firstly, a new coronavirus emerged in Wuhan, China, sparking a pandemic of acute respiratory syndrome in humans. Corona virus disease-19 (COVID-19) was declared as a pandemic after the infection spread globally and disease caused by the new type of coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was named as COVID-19. The virus originated from bats and has been passed to humans. Initially, SARS-CoV-19 infects respiratory system an acute serious viral infection mainly developed with over a million people worldwide were transmitted rapidly in a few months. SARS-CoV-19, progress a moderate to serious severe respiratory symptoms such as headache, cough, and breathlessness. Also, digestive system symptoms include nausea, vomiting, and stomach pain.  Although the precise of the mechanism of inflammation unclear but this virus firstly use the angiotensin converting enzyme 2 (ACE2) receptor of the alveolar cells of lung tissue causing inflammation and cell death.  Then virus spreads and affects other important organ and tissues with complex pathophysiological alterations, the coronary disease, pulmonary disease, chronic kidney disease and chronic liver disease are the most prevalent comorbidities among patients. In COVID-19 infection therapy lots agents recommended. Unfortunately, there is no clear effective drug for treatment. This review presented potential pathogenic pathway of the SARS-CoV-19 infection and symptoms in the patients and given the information about the negative effects on different systems in the respiratory, cardiac system, nervous system, gastrointestinal system, and urinary tract.